2009
DOI: 10.1111/j.1526-4637.2009.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Pain, PTSD, mTBI, and Heart Rate Variability in Veterans of Operation Enduring and Iraqi Freedom: A Pilot Study

Abstract: These preliminary findings support the high prevalence of depressed HRV and P3 among veterans seen in a level II Polytrauma Center. The findings also suggest a possible synergistic effect of pain, PTSD, and mTBI on depressed HRV. The nature and implications of these relationships require additional research to elucidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 54 publications
3
54
0
4
Order By: Relevance
“…For instance, HRV was found to be lower in chronic low back pain patients with moderate levels of self-reported functional impairment compared to those with minimal levels of impairment [12]. Consistent with our findings, the previous literature also has found increased levels of anxiety to be associated with lower HRV in individuals with post-myocardial infarction [17] and more pain has been associated with lower HRV in returning OEF/OIF veterans [40]. Thus, our findings in general support and extend previous research in that we found better physical functioning was related to increases in HRV in chronic benign pain while pain sensations were associated with decreases in HRV.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, HRV was found to be lower in chronic low back pain patients with moderate levels of self-reported functional impairment compared to those with minimal levels of impairment [12]. Consistent with our findings, the previous literature also has found increased levels of anxiety to be associated with lower HRV in individuals with post-myocardial infarction [17] and more pain has been associated with lower HRV in returning OEF/OIF veterans [40]. Thus, our findings in general support and extend previous research in that we found better physical functioning was related to increases in HRV in chronic benign pain while pain sensations were associated with decreases in HRV.…”
Section: Discussionsupporting
confidence: 93%
“…We identified traumatic brain injury (TBI) in addition to other neurological, mental health, and medical comorbidities using algorithms validated for use with ICD-9-CM codes and which were used in our previous studies [14]. Consistent with prior studies using administrative data, identification of all comorbidities except TBI (where policy recommends a single diagnosis for TBI) required individuals to be diagnosed two times at least seven days apart for outpatient diagnosis or a single inpatient diagnosis [15,16].…”
Section: Comorbiditiesmentioning
confidence: 97%
“…Postulated mechanisms include sympathetic activation, which may over time result in cardiac autonomic dysfunction. 32,33 However, the low diagnostic yield of cardiac catheterization among women veterans might also indicate that screening and referral for catheterization needs improvement. Additional research is needed to better understand the referral patterns at the VA; unfortunately, details about the description and nature of chest pain were not available in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Depression, anxiety, and other psychological disorders can also manifest physical symptoms, such as chest pain, even in the absence of CAD. [29][30][31] Because depression and PTSD are associated with decreased quality of life, persistent chest pain, increased cardiovascular risk, and worse cardiovascular outcomes, [32][33][34][35] the high rates observed in the veteran population clearly warrant attention.…”
Section: Discussionmentioning
confidence: 99%